Plant stature of aromatic rice genotypes in the environment of Bangladesh. - Shahidullah, S. M.; Musa, Mohamed Hanafi; Ashrafuzzaman, Muhammad; Hakim, M. A.; Karim, Mohammad Rezaul (Triveni Enterprises, Lucknow, 2011)
Plant stature of a rice crop is an important selection criterion. As plant height is a quantitative trait it is influenced by environmental conditions. A field experiment was conducted with 40 rice genotypes to assess the fluctuation and stability of plant height in a series of 16 environmental situations. The effects of genotype (G), environment (E) and all the components of GxE interaction were highly significant. Among the genotypes, Jamai sohagi was extremely sensitive (bi = 1.37) to environmental changes, and indicating lowest adaptability over the environments. Plant height of seven genotypes viz. Basmati PNR346, Benaful, BRRIdhan28, BRRIdhan38, BRRIdhan39, Gandho kasturi and Neimat, having the bi values between 0.59 and 0.72, showed high stability against environmental changes. The otherseven genotypes viz. Badshabhog, Basmati Tapl-90, Kamini soru, Khazar, Laljira, Sarwati and Ukni madhu expressed only nonlinear sensitivity (S2di = 90-181)) and thus unpredictable fluctuation. Twenty one genotypes indicated their average stability (bi = 0.91-1.15) over the environments.